HISTORICAL ANALYSES OF THE BATTLES OF THE SELEUCID EMPIRE (2022)
Ancient authors such as Plutarch, Appian and Diodorus Siculus narrate the histories of the several wars that the Seleucid Empire was involved in. Modem authors draw from the works of ancient authors in discussing governance and exclusiveness of the Seleucids in their relationship with the people in their sphere of control, the personalities . of the Seleucid rulers, especially Seleucus I Nicator and Antiochus III the Great, with little attention paid to the battles of the Seleucid Empire. This paper, therefore, attempts to examine the battles fought by the Seleucid Empire, with a view to interrogating the strategies employed during the battles, the essence of some of these battles and the peace treaties drawn in the course of the battles. The paper adopts John Mearsheimer's theory of offensive realism as its aid in the discourse of the frequent battles. The paper also implements a historical methodology as it further provides a trajectory of the battles and some of the strategies deployed by the Seleucids in engaging heir enemies. Studies that may examine the tactics employed by the Seleucid rulers in the Syrian wars are recommended.